Developing a valid instrument to measure how personal characteristic and leader behaviour affect team performance / Mohamad Azmi Nias Ahmad …[et al.] - Ahmad, Mohamad Azmi Nias; Abdul Hamid, Siti Fadhilah; Mohd Asmi, Nurul Syazhera; Md Pauzi, Suria Fadhillah; Ahmad Zaini, Azniza; Md Zeni, Syahida (2016)
Kelab Memanah UiTM Pahang has appointed its team captain among the student as a coach since there is no new coach to be appointed due to unprecedented circumstances. Since the team need to maintain high team spirit, confidence and performance, the effectiveness of peer leader is still obscured. This study presents a tool for measuring personal characteristics, leader behaviour and performance. This study proposed a 34-item scale. There are 30 archers participated in this study. Using partial-least-square structural equation modelling (PLS-SEM), this study proposed a reliable tool to efficiently measure the constructs under study.